Shariah Value Logic to Enhance NPD Performance - Mansur Chadi Mursid (International Journal of Islamic Business and Economics (IJIBEC), 2018)
To analyze shariah value logic as the role mediating in the relationship between NPD Innovation and NPD Performance. We purposed shariah value logic as mediating role in this study. The questionnaires will be given to only the managers of LKMS (the board of shariah micro finance) in Pekalongan, Indonesia with total 246 responden from 24 LKMS (Baitul Maal wa Tamwil, Baitul Tamwil, Kospin Jasa Shariah, and KSPP Shariah). Shariah Value Logic significantly affect to Customer Brand Trust. Research limited in muamalah, future research can exploring in ebadat. LKMS adapted shariah value logic to get customer brand trust. Shariah value logic as the new variable and theory concept. Indirect, NPD Innovation positive significantly affect to NPD Performance with shariah value logic and customer brand trust are as mediating role.